2010
DOI: 10.1007/s00595-009-4138-y
|View full text |Cite
|
Sign up to set email alerts
|

Xanthogranulomatous cholecystitis complicated with primary sclerosing cholangitis: Report of a case

Abstract: Patients with primary sclerosing cholangitis (PSC) are at an increased risk for biliary tract carcinoma. The preoperative diagnosis of a biliary tract tumor as a malignancy is difficult, even using new modalities such as multidetector computed tomography (MD-CT), magnetic resonance cholangiopancreatography (MRCP), endoscopic retrograde cholangiography (ERC), and (18)F-fluorodeoxyglucose positron emission tomography (FDG-PET). Surgery is considered to be first line of treatment when these examinations suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…There has been a case report of XGC in a patient with PSC by Mori et al. [36] in 2010 and reports of xanthogranulomatous cholangiopathy in patients who underwent transplantation for PSC [37] . However, to the best of our knowledge, our patient is the first case of concomitant UC, PSC, and XGC, along with the presence of intramucosal adenocarcinoma in the distal CBD.…”
Section: Discussionmentioning
confidence: 99%
“…There has been a case report of XGC in a patient with PSC by Mori et al. [36] in 2010 and reports of xanthogranulomatous cholangiopathy in patients who underwent transplantation for PSC [37] . However, to the best of our knowledge, our patient is the first case of concomitant UC, PSC, and XGC, along with the presence of intramucosal adenocarcinoma in the distal CBD.…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that GLUT-1 together with GLUT-3 is the most important isotype for understanding 18 F-FDG uptake in WBCs. 9 Although several authors have previously reported XGC mimicking gallbladder carcinoma with a false-positive result on 18 F-FDG PET, 27,28 no correlative clinical report has been revealed between 18 F-FDG accumulation and the immunohistochemical expression of GLUTs in the resected XGC specimens. In our case, GLUT-1 and GLUT-3 were both positively expressed in inflammatory cells in the XGC gallbladder wall where 18 F-FDG was accumulated on PET examination.…”
Section: Discussionmentioning
confidence: 99%
“…FDG-PET gave false-positive results in all four cases where this test was performed (Table 1). Xanthogranulomatous infl ammation, which contributes to the FDG uptake, 15 has not always been reported to accompany systemic infl ammatory responses (Table 1). Thus, we suggest that FDG-PET may give false-positive results in XGP patients, regardless of whether systemic infl ammatory responses are present.…”
Section: Discussionmentioning
confidence: 99%